DESENVOLVIMENTO E AVALIAÇÃO FARMACOCINÉTICA DE NANOPARTÍCULAS DE PLGA E PLGA-PEG CONTENDO CURCUMINA - Nascimento, Thuane Castro Frabel do (2011)
The polymeric nanoparticles present great importance in the pharmaceutical field due to be colloidal systems, which have interesting physicochemical properties, such as the reduced size, the large superficial area and the superficial charge making them efficient systems for applying in the controlled releasing of drugs. The curcumin is a yellow pigment, which is present in the Curcuma longa having low toxicity and a large range of pharmacological activities. It is among the most promising effective chemopreventive agents and/or antitumorals. However, its therapeutical use has been limited owing to its low aqueous solubility, its high decomposition rate in low or neutral pH, besides the fast metabolism and systemic elimination resulting in low bioavailability. In this study poly(lactic-co-glycolic acid) (PLGA) and blends of PLGA with polyethylene glycol (PEG) nanoparticles containing curcumin were obtained through the solvent emulsification-evaporation technique aiming to improve its pharmacokinetic properties. After the method validation by high performance liquid chromatography (HPLC) for the quantitation of curcumin, the nanoparticles were assessed regarding the average diameter and the encapsulation efficiency. Both formulations obtained the encapsulation efficiency higher than 75% and the average diameter was not higher than 200 nm. The in vitro releasing study showed that the nanoparticles sustained the curcumin release and the PEG presence in the formulation contributes to the increased rate of curcumin release. A liquid chromatography mass spectrometry method was developed and validated and showed to be very sensitive, reproductive and specific for curcurmin in rat plasma. After oral administration in rats, the PLGA and the PLGA-PEG blends nanoparticles were able to keep a sustained release of curcumin, with significantly different results between formulations. The iv PLGA and PLGA-PEG nanoparticles increased the half-life time of curcumin in approximately 4 and 6 h, respectively. Comparing the aqueous suspension of curcumin, the mean plasma concentration of curcumin from the PLGA and PLGA-PEG nanoparticles were 2.9 and 7.4 -fold higher, respectively. The distribution and the metabolism of curcumin were reduced when carried by the nanoparticles, mainly by the PLGA-PEG nanoparticles. The bioavailability of curcumin from the PLGA-PEG nanoparticles was 3.5 -fold greater than that of curcumin from PLGA nanoparticles. Compared to the curcumin aqueous suspension, the PLGA and PLGA-PEG nanoparticles increased the curcumin bioavailability in 15.6 and 55.4-fold, respectively. These results suggest that PLGA and mainly PLGA-PEG nanoparticles are promising carriers of curcumin for oral administration.